2019
DOI: 10.1101/607754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain age prediction reveals aberrant brain white matter in schizophrenia and bipolar disorder: A multi-sample diffusion tensor imaging study

Abstract: Word count abstract: 249/250 | Main text: 3810/4000 Number of Figures 2 | Tables: 1 | Supplementary information: 1 document Abstract (249/250 words)Background: Schizophrenia (SZ) and bipolar disorders (BD) share substantial neurodevelopmental components affecting brain maturation and architecture. This necessitates a dynamic lifespan perspective in which brain aberrations are inferred from deviations from expected lifespan trajectories. We applied machine learning to diffusion tensor imaging (DTI) indices of w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…In line with recent studies demonstrating high age prediction accuracy based on diffusion‐weighted imaging data (Beck et al, 2021; Cole, Marioni, et al, 2019; Richard et al, 2018; Smith et al, 2020; Tønnesen et al, 2020), the WM prediction showed higher accuracy compared to the GM model, of which the accuracy corresponded to our previous UK Biobank studies (de Lange et al, 2019; de Lange, Barth, Kaufmann, Anatürk, et al, 2020; de Lange, Barth, Kaufmann, Maximov, et al, 2020). Importantly, we found unique contributions by both models, suggesting that the diffusion‐based WM model may pick up variance not explained by the T1‐based GM model.…”
Section: Discussionsupporting
confidence: 88%
“…In line with recent studies demonstrating high age prediction accuracy based on diffusion‐weighted imaging data (Beck et al, 2021; Cole, Marioni, et al, 2019; Richard et al, 2018; Smith et al, 2020; Tønnesen et al, 2020), the WM prediction showed higher accuracy compared to the GM model, of which the accuracy corresponded to our previous UK Biobank studies (de Lange et al, 2019; de Lange, Barth, Kaufmann, Anatürk, et al, 2020; de Lange, Barth, Kaufmann, Maximov, et al, 2020). Importantly, we found unique contributions by both models, suggesting that the diffusion‐based WM model may pick up variance not explained by the T1‐based GM model.…”
Section: Discussionsupporting
confidence: 88%
“…In line with recent studies demonstrating high age prediction accuracy based on diffusion imaging data [37,63,89,90,91], the WM prediction showed higher accuracy compared to the GM model, of which the accuracy corresponded to our previous UK Biobank studies [10,11,54]. Importantly, we found unique contributions by both models, suggesting that the diffusion-based WM model may pick up variance not explained by the T1-based GM model.…”
Section: Modality-specific and Regional Effectssupporting
confidence: 91%
“…While age prediction models have been used for more than a decade to generate imaging-based biomarkers [20], the approach continues to be developed and extended (see for example [3,9,56,31,49,58]). Although not covered in the current study, an increasingly common scenario involves combining data from various cohorts and scanners, which poses additional challenges related to site-and scanner-dependent variance [25]. Improving methods for site/scanner adjustments [59,60], or incorporating uncertainties into the predictions [61,62], represent promising avenues for further developing robust and valid biomarkers for brain health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…[42,40,38]). In other words, it provides the same results as regressing out chronological age from brain age delta and using the residuals [41,6,9,25,12], or including chronological age as a covariate in regressions/correlations between brain age delta and other variables of interest [41,42,49,31]. The orange line shows the linear fit applied to model the age bias.…”
Section: Age-bias Correctionmentioning
confidence: 99%
See 1 more Smart Citation